Analisis Implementasi Fuzzy-Dijkstra untuk Pencarian Rute Optimal pada Wireless Sensor Network menggunakan MATLAB - Abirafdi Sukma Nazhifan; Mochammad Hannats Hanafi Ichsan; Sabriansyah Rizqika Akbar (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2022)
In the science of computer network connections, network mapping makes use of a number of well-organized programs. However, regardless of the application, network mapping to identify the optimal path is still minimal. This is due to the fact that computer network designers often ignore the idea that data transmission is accelerated and unnecessary delays can be avoided by choosing the optimal path on the network. This study discusses finding the optimal route by combining the Fuzzy Sugeno logic method and the Dijkstra algorithm in the Wireless Sensor Network (WSN). Sugeno's Fuzzy Algorithm is an algorithm that analyzes input, evaluates a number of possible paths and produces solutions. Dijkstra's algorithm works by relying on the weights issued by Fuzzy Sugeno which has iterations to find the point whose distance from the starting point is the shortest. This study is intended to determine the results of data visualization in MATLAB, the optimal route that can be generated, and the distance used by this Fuzzy-Dijkstra algorithm. From this research, data obtained from experiments with nodes 10 to 1000 on distance and QOS parameters in the form of throughput, packet loss, delay. Based on the results of the study, it can be concluded that the Fuzzy Sugeno algorithm is good at determining the optimal route from nodes that have been plotted randomly and have been given a weighted QOS value that is in accordance with the TIPHON parameter assessment standard.